Indonesian Islamic Moderation for National Defence - Saleh, Ahmad Junaidi (Advances in Social Sciences Research Journal, 2020)
The phenomenon movement of Moslems on early 21th century is shown hight intensitily. This is indicated by Islamic political movements which are dominated by non-mainstream Islamic movements which have influence many maps of Islamic movements, include in Indonesia. On moderate side Islamic groups as mainstream still appear with their old patterns of displaying open harmonious variants of Islam, tolerant and modest locality of Islamic traditional and building Islamic civilization and humanity in Indonesia. As the majority of the world’s most Moslem population in a pluralistic and pluralist community, existence of moderate Islam is very important in the national defense system. This article uses a qualitative approach with data sources from references and literature relating to Islamic moderation. The validity and reliability of the data is done by triangulation reference. The method on this study is a qualitative method. Data collection techniques are literature and documentation. From this study, the results are obtained that the presence of moderate Islam will be able toward off the dynamics of threats, which move from a national defense system. Keywords: Islamic moderation, State Defence